Determinants of Maqasid al-Shari’ah-Based performance measurement practices: the case of Malaysian Islamic banks - Mohamad, Muslim Har Sani; Ali, Muhammad Ahmar; Mohd Shariff, Ros Aniza (International Islamic University Malaysia, 2016)
This study aims at investigating the practice of Maqāṣid al-Sharī‘ah based performance measures, determinants of its successful implementation and its impact on Islamic bank performance. Understanding the extent that Islamic banks are institutionalizing Maqāṣid al-Sharī‘ah based performance measures (Maqāṣid PMs) will provide greater insights into the development of Islamic banking in achieving the Islamic financial system objectives. A total of 146 questionnaires were distributed to all business units of all 16 Islamic commercial banks in Malaysia. The study found that contrary to the contemporary scepticism, Islamic banks in Malaysia are indeed promoting and committed to achieving Maqāṣid al-Sharī‘ah with the relevant performance measures in place. Specifically, the study found that performance measures for public interest and fairness are widely used by the Islamic banks. With communication technology and regulatory compliance, use of Maqāṣid al-Sharī‘ah based performance measures as Islamic banks’ performance driver becomes more potent.